An Analysis of Negligence Committed by Members of the Indonesian National Police (POLRI) in a Criminal Case: A Case Study of Decision Number 55/Pid.B/2024/PN Plk - Sarah; Kristian; Pramitha, Claudia Yuni (Journal of Law, Politic and Humanities, 2025)
Police officers' culpa in carrying out their duties has a serious impact on the justice system and the accountability of the police institution. This study analyzes the case of Decision No. 55/Pid.B/2024/PN Plk to evaluate the legal process in dealing with the culpa of officers that led to death and serious injury. The results showed that the lenient verdict against the defendant did not reflect substantive justice and created a crisis of public confidence in the legal system. Lack of transparency in investigations and weak regulations on the use of force in the police force exacerbate this situation. Inequality in law enforcement between officers and civilians exacerbates injustice in the criminal justice system. In recent years, a number of cases involving members of the police as perpetrators of crimes, especially those related to violence, have reduced the positive image of the police in the eyes of the public. One of the most prominent cases was a shooting committed by a police officer in Palangkaraya, Central Kalimantan, which involved culpa and abuse of authority. From 2023 to 2025, two shooting incidents involving members of the National Police occurred in this region, with most of the victims being civilians. These cases illustrate not only individual errors in the performance of duties, but also weaknesses in POLRI's internal control system. These shootings by police officers raise questions about causal factors, such as culpa in supervision, abuse of authority, mental health problems, and inability to manage emotions under pressure. Therefore, reforms in oversight mechanisms, increased transparency in the judiciary, and strengthened regulations related to police accountability are needed to ensure fairer law enforcement. In addition, protection for victims must be strengthened so that justice is not only oriented towards the perpetrators but also towards the rights of victims and their families. Legal reforms should include improvements to police operational standards so that the use of force remains in accordance with the principles of human rights and the rule of law. These reforms are expected to make the criminal justice system more effective in enforcing the law fairly and increase public confidence in the police institution.